Long-term effectiveness, safety and immunogenicity of the biosimilar SB2 in inflammatory bowel disease patients after switching from originator infliximab - Sarah Fischer; Sarah Cohnen; Entcho Klenske; Heike Schmitt; Francesco Vitali; Simon Hirschmann; Andreas Ramming; Sebastian Zundler; Timo Rath; Sabine Krebs; Frank Dörje; Wolfgang Uter; et al. (Therapeutic Advances in Gastroenterology, 2021)
Background: Long-term data on inflammatory bowel disease (IBD) patients switched from originator to biosimilar infliximab SB2 are lacking. The aim of the conducted study was to investigate the effectiveness, immunogenicity and safety of a large prospectively followed-up IBD patient cohort that was entirely switched from originator infliximab to biosimilar SB2 treatment. Methods: This was a prospective, single-center, longitudinal, observational study describing clinical outcomes in IBD patients, over an 80-week period following switch from originator infliximab to SB2. Primary outcome measures were change of disease activity [Harvey-Bradshaw Index for Crohn’s disease (CD), partial Mayo Score for ulcerative colitis (UC)], C-reactive protein (CRP), infliximab trough levels (TLs), anti-drug antibodies (ADAs) and adverse events. Results: One hundred and forty-four IBD patients (94 CD, 50 UC), with median duration of 30.5 months’ (range 2–110) treatment with originator infliximab were evaluated. Mean change of disease activity compared with baseline was −0.9 (SD 2.6), –0.4 (2.2) and –0.4 (2.0) in CD; 0.1 (1.1), 0.1 (1.1) and 0.1 (1.3) in UC patients at weeks 24, 48 and 72. Median infliximab TLs were 6.2 µg/ml (interquartile range 2.3–12.2), 5.0 µg/ml (2.7–10.0), 6.6 µg/ml (3.5–12.4) and 5.1 µg/ml (2.7–10.9) at baseline and weeks 24, 48 and 72. Median CRP levels were within normal ranges throughout the study. After the switch, 9.8% of the patients developed new ADAs. Persistence on SB2 was 90% (95% confidence interval 0.85–0.95), 79% (0.72–0.86), 72% (0.64–0.80) at weeks 26, 52 and 78. Serious adverse events occurred in 11 patients. Conclusion: Over the individual patient follow-up of 80 weeks, switch to biosimilar SB2 from originator infliximab does not result in increased disease activity or changed immunogenicity patterns. The switch to SB2 was well tolerated.